Internments after the First World War - Bajc, Gorazd (Acta Histriae, 2018)
In November 1918, at the end of World War I, the new Italian authorities arrested several persons in the territory of Venezia Giulia, Rijeka (Fiume) and some parts of Dalmatia and interned some of them in the interior of Italy. A detailed examination of many documents and lists that are kept in Roman and Trieste archives reveal that around 850 civilians were interned, including women. Internments after the First World War in the Slovenian/Croatian-Italian contact area have still not received in-depth analysis; however, even less is known about the internment of women.
Keywords: 20.st.; internacije; Italija; nasilje; svetovna vojna 1914-1918; tranzicija; zgodovina; zgornji Jadran; ženske